Determining the relationship between the speed of motion of large permanent magnets and the trajectory of implants in magnetic stereotaxic systems - Hankun, J.; Avrunin, O. G. (Biophysical Bulletin, 2024)
Background: The magnetic stereotaxic system is a new type of neurosurgical intervention that is in the experimental stage. This method allows the implant to be controlled non-contact by an external magnetic field, allowing it to move along an arbitrary trajectory to a lesion located in a deep structure of the brain tissue to deliver hyperthermia to the lesion site or deliver medication through a catheter. In previous studies, we have found that it is completely feasible for the implant to move along the arc trajectory, so we need to determine the relationship between the movement speed of the large permanent magnet that constitutes the external magnetic field and the implant movement trajectory, so as to control the implant movement more precisely.Objectives: Investigate the effect of the speed of motion of large permanent magnets, which constitute the external magnetic field, on the trajectory of implants (small permanent magnets).Materials and Methods: Firstly, three sets of computer simulation experiments were conducted, each group of experiments only changed the operating speed of large permanent magnets, and the changes in the trajectories of small and medium-sized permanent magnets in the three sets of experiments were observed and compared. After that practical experiments are carried out to validate the results of the computer simulation experiments by means of the slide rail system controlled by an Arduino microcontroller.Results: The relationship between the moving speed of the large permanent magnet and the trajectory of the small permanent magnet was determined by simulation experiments, and the changes in the strength of the surrounding magnetic field during the movement of the implant were calculated. Afterwards, it was verified by practical experiments. The faster the large permanent magnet moves, the shorter the distance that the small permanent magnet moves along the linear trajectory, and the longer the distance that moves along the arc trajectory; The slower the large permanent magnet moves, the longer the small permanent magnet travels along a straight trajectory and the shorter the distance it travels along an arc trajectory.Conclusions: In this research, we have determined the relationship between the running speed of the large permanent magnet that constitutes the external magnetic field and the implant's moving trajectory by combining computer simulation experiments with practical experiments, i.e., the faster the large permanent magnet moves, the shorter the implant's moving distance is along a straight line trajectory, and the longer the moving distance is along a curved line trajectory. This means that we can control the distance and steering angle of the implant more accurately, which makes the study of the magnetic stereotaxic system further, and lays a theoretical foundation and provides a large amount of experimental data for the implant to be able to reach the diseased site located in the deep structure of the brain tissue along complex pathways in neurosurgical interventions with the participation of the magnetic stereotaxic system.